The interplay of different sensory attributes in lingonberry nectars with sucrose and high intensity sweeteners - Kjersti Aaby; Josefine Skaret; Ingunn Berget; Paula Varela (Applied Food Research)
Lingonberries are associated with several health benefits and have a distinct flavour, but the berries are also bitter, astringent and sour. Addition of a sweetener, traditionally sucrose, is necessary to increase palatability of lingonberry products. Meanwhile, there is a goal to reduce sugar consumption. Alternative sweeteners may, however, have different sensory profiles compared to sucrose. The aim of the study was to understand the changes in the sensory profiles of lingonberry juice sweetened with high intensity sweeteners (sucralose, aspartame or acesulfame K) alone or in combination (1/1), compared to sucrose (10 %). The sensory profiles of the lingonberry nectars were evaluated by quantitative descriptive analysis (QDA) and temporal-check-all-that-apply (TCATA). According to both QDA and TCATA results, the nectars sweetened with aspartame and the blend of aspartame and acesulfame K were most like the nectar with sucrose. These beverages were characterised by more sweet taste, fullness and sour flavour and less pungent sensation, acidic taste, and astringency than the other nectars. The nectars that differed most from the reference were those sweetened with sucralose, acesulfame K and the blend of aspartame and sucralose. The nectar with the blend of acesulfame K and sucralose had a similar temporal profile to the sucrose sweetened juice but was evaluated differently in the QDA. QDA and TCATA provided complementary insights, with QDA identifying static attributes and TCATA capturing dynamic changes in sensory perception over time.